Assessment of the micro-mechanical fracture processes within dissimilar metal welds. (March 2019) - Brayshaw, W.J.; Cooper, A.J.; Sherry, A.H.
Abstract: Dissimilar metal welds represent a challenge for structural integrity assessments due to the different compositions of component materials, inhomogeneous microstructures and variation in material properties across short length scales. These variations influence the evolution and distribution of plastic strain surrounding crack-tips and stress concentrators, and hence fracture behaviour. In the current work, fracture toughness testing and subsequent fractographic analyses have been conducted on dissimilar metal weld test specimens, comprised of SA508 Gr. 4 N ferritic steel joined to AISI 316 L(N) stainless steel via a filler weld of Alloy 82. The results show a variation in crack growth mechanisms depending on the material within which the crack-tip was positioned. For the fatigue pre-crack, located in the SA508 Gr. 4 N heat affected zone, the initial crack growth was by a micro-shear mechanism. When the growing crack reached the Alloy 82 filler material, ductile tearing was observed. Porosity originating from the welding process and ductile tearing have been characterized using 3D X-ray computed tomography. Significant hardening, inferring the accumulation of plastic strain was quantified via microhardness measurements within the Alloy 82. Ductile void growth extended over approximately 1000 μ m below the fracture surface, with a peak void volume fraction of 0.007. These data provide a useful basis for the calibration of ductile crack growth models.